FAAH rs324420 Polymorphism: Biological Pathways, Impact on Elite Athletic Performance and Insights for Sport Medicine - Silva, Hugo-Henrique (2023)
Gene variation linked to physiological functions is recognised to affect elite athletic performance by modulating training and competition-enabling behaviour. The fatty acid amide hydrolase (FAAH) has been investigated as a good candidate for drug targeting, and recently, its single-nucleotide polymorphism (SNP) rs324420 was reported to be associated with athletic performance. Given the implications, the biological pathways of this genetic polymorphism linked to elite athletic performance, considering sport type, psychological traits and sports injuries, need to be dissected. Thus, a narrative review of the literature concerning the biological mechanisms of this SNP was undertaken. In addition to its role in athletic performance, FAAH rs324420 is also involved in important mechanisms underlying human psychopathologies, including substance abuse and neural dysfunctions. However, cumulative evidence concerning the C385A variant is inconsistent. Therefore, validation studies considering homogeneous sports modalities are required to better define the role of this SNP in elite athletic performance and its impact on stress coping, pain regulation and inflammation control.